Optimizing Investments in Bulgaria's HIV Response - World Bank (World Bank, Washington, DC, 2018)
Bulgaria has a concentrated but growing HIV epidemic, in which HIV prevalence increased among all population groups over the past decade. This increasing trend in HIV prevalence is particularly marked among men who have sex with men (MSM). For men and women who inject drugs, assuming stable behaviors and program coverage, HIV prevalence is expected to remain above 8 percent and 5 percent respectively. There is an urgent need to shift additional domestic resources towards HIV. Bulgaria was already financing 67 percent of its HIV/AIDS response in 2014 with domestic funding. However, there is an urgent need to fill resource gaps in the overall HIV budget envelope with increased domestic financing. Current annual spending will not, according to this analysis, be sufficient to realise the proposed National Strategic Plan and international targets. The budget will need to be increased to achieve these targets and the increase will need to be larger if technical and allocative efficiency gains are not made. Bulgaria's HIV response requires a shared, long-term vision for sustainable HIV financing that harnesses wider health sector reforms and emerging financing models.